2019
DOI: 10.1088/1748-605x/ab026c
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline cellulose–hyaluronic acid composite enriched with GM-CSF loaded chitosan nanoparticles for enhanced wound healing

Abstract: In recent years, applications of biopolymers such as hyaluronic acid (HA) for wound dressing have attracted more attention. However, the poor mechanical properties of HA-based wound dressings limit their clinical applications. Incorporation of reinforcing agents such as nanocrystalline cellulose (CNC) in HA-based wound dressings can improve their mechanical properties. In addition, controlled delivery of growth factors to the wound site using nanoparticles can significantly improve the healing process. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…In addition, NP applied wounds showed sufficiently lower inflammatory reaction, improved re-epithelization as well as enhance granulation tissue formation. The results suggest that the prepared dressing can be potentially applied in clinical practice for wound treatment [83] .…”
Section: Biomaterials For Wound Managementmentioning
confidence: 90%
“…In addition, NP applied wounds showed sufficiently lower inflammatory reaction, improved re-epithelization as well as enhance granulation tissue formation. The results suggest that the prepared dressing can be potentially applied in clinical practice for wound treatment [83] .…”
Section: Biomaterials For Wound Managementmentioning
confidence: 90%
“…The cell culture exhibited that NIH-3H3 cells can attached to, grow, and proliferate well on the GA-HA-CNC hydrogels, confirming their potential application in wound dressing field. Recently, Dehkordi et al prepared a novel CNC-reinforced hyaluronic acid composite containing nanochitosan loaded with granulocyte macrophage colony stimulating factor (GM-CSF) as an efficient candidate for wound healing (Dehkordi et al, 2019). The resulted composite exhibited interesting features such as high swelling capacity, suitable mechanical characteristics and controlled release of GM-CSF.…”
Section: Nanocellulose For Biomedical Applicationsmentioning
confidence: 99%
“…Furthermore, positively charged CS containing biomaterials could be loaded with growth factors and cytokines to improve their performance in the wound healing process. In a recent study, CS NPs prepared through ionotropic gelation with tripolyphosphate [49] were loaded with granulocyte-macrophage colony-stimulating factor (GM-CSF) as a part of a nanocrystalline cellulose-hyaluronic acid composite prepared by a freeze-drying method [50]. Loading efficiency of GM-CSF was as high as 97.4 ± 1.68% with sustained release of~100% over 48 h and in vivo experiments have shown that composites loaded with encapsulated GM-CSF in CS NPs induce greater wound closure compared to the composite alone [50].…”
Section: Chitosan For Wound Healingmentioning
confidence: 99%